(untitled) (Fiep Bulletin - online, 2011)
Introduction: one of the main complaints of cancer patients is pain. The World Health Organization (WHO) recommended as a priority in the health system the world pain control through the "analgesic ladder" that guides health professionals in the clinical management of this patient. Objective: To make an approach to drug therapy to control cancer pain. Methodology: It is a narrative review held in databases in the Virtual Health Library (BIREME), the foundations of Latin American Literature (LILACS) and International Literature in Health Sciences (MEDLINE) and within the Capes bases CINAHALL and the WEB SCIENCE. Discussion: the control of cancer pain arises from principles such as choice of appropriate analgesic as pain intensity, strictly following the schedule of medication and careful adjustment of doses of medicines, which may change as the patient’s need. It is necessary for the construction of the treatment plan is based on the patient, it is the "authority" in the search for pain control. Conclusion: pharmacological treatment should be consistent with the intensity of the patient’s pain and that is according to the analgesic ladder as proposed by the WHO, therefore minimize the under-identification and under-treatment of pain.